Antibiotic resistance of Aeromonas spp. isolated from diseased walking catfish (Clarias sp.) - DINI SISWANI MULIA; Alim Isnansetyo; RARASTOETI PRATIWI; WIDYA ASMARA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mulia DS, Isnansetyo A, Pratiwi R, Asmara W. 2021. Antibiotic resistance of Aeromonas spp. isolated from diseased walking catfish (Clarias sp.). Biodiversitas 22: 4839-4846. Aeromonas spp. is known to be pathogenic to freshwater fish, including catfish. Antibiotics are often used to overcome bacterial attacks. However, the indiscriminate use of antibiotics, especially at incorrect doses and frequencies, could result in the emergence of resistant bacteria. The presence of resistance genes is also suspected to trigger the resistance potential of Aeromonas sp. against antibiotics. The objective of this study is to characterize the resistance genes of Aeromonas spp. isolated from diseased walking catfish (Clarias sp.). Ten Aeromonas spp. were isolated from infected walking catfish cultivated in Java. The resistance genes assessed included tetA, strA-strB, and qnrA. The antibiotics tested consisted of ampicillin (AMP), erythromycin (ERY), oxytetracycline (OXT), kanamycin (KAN), enrofloxacin (ENRO), and chloramphenicol (CHL). Results showed that some Aeromonas spp. had at least one out of the three genes assessed (i.e., tetA and strA-strB) but none had the qnrA gene. Aeromonas spp. were sensitive to KAN, ENRO, and CHL but resistant to AMP, ERY, and OXT. Thus, KAN, ENRO, and CHL are effective antibiotics for treating fish infected with Aeromonas spp.